PEMETAAN PENCIPTAAN NILAI PADA AKTIVITAS PENGADAAN DAN PENJUALAN SKRAP LOGAM KALENG MENGGUNAKAN VALUE STREAM MAPPING UNTUK MENGURANGI WASTE DI PT ANISA JAYA UTAMA - Siti Zaenab Nur Hasanah; Dedy Setyo Oetomo; Afif Fawa Idul Fata (Asosiasi Dosen Muda Indonesia, 2023)
Industrialization is an alternative development model needed by the country to spur economic processes. Apart from accelerating the economy, the development of industrialization also has impacts that need to be watched out for, including the presence of a waste industry. One of the companies that manages the waste, namely PT. AJU is also a service company for the procurement and sale of metal waste (metal scrap) in Karawang. The metal scrap studied is canned metal scrap, which is wasteful in the procurement and sales process. So that efforts are made to minimize the waste that occurs. This research uses the Value Stream Mapping method with VALSAT analysis. Based on the research results, the most common types of waste are waiting (28%), inventory (24%), and movement (20%). Then the mapping tools that will be used based on the results of converting the questionnaire scores into the VALSAT matrix are Process Activity Mapping (33%), Supply Chain Response Matrix (20%), and Demand Amplification Mapping (17%). The Value Added Ratio (VAR) before the repair has a value proportion of 3%, while after the repair analysis the VAR value becomes 9%.